Impact of organic solvents in combination with redox-couples on magnitude of seebeck coefficient, and electrical current in thermoelectric generators. (2021) - Laux, Edith; Jeandupeux, Laure; Homsy, Alexandra; Hofmann, Martin; Potty, Philippe; Keppner, Herbert
Abstract: In previous work it was shown that Ionic Liquids as active substances in thermoelectric generators have the potential to reduce the thermal conductivity as compared to Solid State materials used in conventional TEGs. Furthermore, it was observed that the Seebeck coefficient could be significantly increased. After a large variety of experiments, it appears that the remaining bottleneck coming to high performance TEGs is, first finding ILs with increased negative Seebeck coefficient, and, second sufficient current extraction. Looking at the current it appears, that higher extractions for a given redox-couple concentration are favoured at reduced viscosity. On the way to explore the effect of viscosity-induced current limitation, in a first step, the Ionic liquids are substituted by a low-viscosity organic solvent such as propylene carbonate (PC). The results showed that, indeed, the thermo-current increases significantly. It was further found that the Seebeck coefficient (SE) using PC exhibited values as high as 1.7 mV/K. Such high values were in previous work rather attributed to the use of ionic liquids. Surprisingly, by adding up to 10% of water to PC, the increased current allowed doubling the power, compared to pure PC. The paper studies the effect of combinations of solvent and redox-couples and tries to correlate the effect of water in PC looking at physical properties such as viscosity, but also the effects of charged carrier-attachment at the electrodes.